The social psychology of intergroup reconciliation - Nadler, Arie; Malloy, Thomas E.; Fisher, Jeffrey D. 1949- (Oxford University Press, 2008)
This text focuses on the removal of psychological barriers (e.g. a lack of trust, feelings of victimisation, perceived lack of power) as a way to end conflict. The book takes the stance that social psychology is uniquely equipped, both theoretically and methodologically, to deal with this challenge.